Marrying Off Sons and Daughters: Attitudes towards the Consent of Parents and Guardians in Early Modern Sweden - Korpiola, Mia (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2005)
Curate Samuel Josephi Lithovius of Limingå (Liminka) in Ostrobothnia was one of the six representatives of the clergy of the diocese of Åbo (Turku) at the diet of Stockholm in 1647. At the diet, however, he was accused by his fellow clergymen of having performed an irregular solemnization (på oordentligit wijs - - hadhe sammanwigdt) at the manor of Åhrsta outside the city of Stockholm. By doing this, he had usurped the authority of another priest and ‘confirmed the madness (galenskap) and disorder with which the parties had commenced their marriage’ for a sum of money. By his actions, he had compromised the whole estate (uppålagdt heela ministerio - - een elack notam).